The “Banksy Effect” and Street Art in the Middle East - DeTurk, Sabrina (SAUC - Street Art and Urban Creativity (repository), 2015)
The English street artist known as Banksy has in recent years become an important figure in the contemporary art world, garnering both critical acclaim and commercial success with his work. The “Banksy effect” is a term coined to describe the increased interest in street art that has emerged in the wake of Banksy’s popularity. Although the Banksy effect is not universally applauded, it offers a useful lens through which to consider the emergence of street art as a means of popular expression in the Middle East and North Africa (MENA) region. This paper considers three places in which street art has been intentionally deployed as a vehicle of political protest or as a means to generate tourism in the face of political unrest: street art in the Palestinian territories; street art in Egypt, particularly Cairo; and the Djerbahood project in Tunisia. A brief discussion of the way in which street art is created and received in each particular area is provided, followed by some observations on how the Banksy effect may be at play in that particular context. The paper concludes that the idea of the Banksy effect has relevance in discussions of street art in the MENA region and that both the positive and negative aspects of the Banksy effect are seen in the region.